Aurora Observing and Recording Nature's Spectacular Light Show - Bone, Neil (The Patrick Moore Practical Astronomy Series, 2007)
The uniquely beautiful light display of an aurora is the result of charged particles colliding with tenuous atmospheric oxygen and nitrogen, more than 60 miles above the Earth, when the magnetosphere is disturbed by changes in the solar wind. Often - and incorrectly - regarded as being confined to high northern and southern latitudes, major auroral displays are visible from even the southern USA and the south of England, and occur perhaps twenty times in each eleven-year sunspot cycle. Major auroral storms always cause great interest and excitement in the media, and of course provide practical astronomers with the opportunity to study and image them. This book describes the aurora from the amateur observational viewpoint, discusses professional studies of auroral and geomagnetic phenomena to put amateur work in context, and explains how practical observers can go about observing and recording auroral displays.